(3GdZjdGfjGJs - (3eMeO Hf YHO Gddg Hf EHQGgje GdTGaYj GdHRGR, CHh HcQs
(3ChdgG (B:s
(3CNHQfG GdTjN CHh eMeO GdMSf Hf YHO Gdedc Hf eMeO Hf jhSa Yf Ydi Hf CHj WGdH bGd (B: (3cfJ LGdSkG YfO GdfHi Udi Gddg Ydjg hSde haNPg Ydi aNPi GdMOjK s
(3BNQgG (B:s
(3ef MOjK GdfHi Udi Gddg Ydjg hSde (B: (3GaThG GdSdGe hCWYehG GdWYGe hUdhG GdCQMGe hUdhG hGdfGS fjGe JONdhG GdLfI HSdGe s
(3GdfSNI HgG MhGTs
(3QhGjI CHh WGdH eMeO Hf eMeO Hf EHQGgje Hf ZjdGf J SfI (B440 (3GdfSNI ai CMO YTQ LRAs
(3G hHBNQ cd LRA YOI SeGYGJ hbQGBJ fajSI LOkG ef GdbQfjf GdNGeS hGdSGOS hYdjgG NWhW GdYdeGAs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg GdMQe Gdeci(B((3MOjK (B579) s
Keywords: (3GdMOjK h GdeUWdMs